Penerapan Teknologi Budidaya Tanaman Stroberi Di Desa Pangkalan Kabupaten Indramayu - Aa Setiawan Aa Setiawan; Yudhy Kurniawan; Wardika (Journal of Applied Community Engagement, 2021)
The geographical condition of Indramayu, which is in the lowlands, is not the right land for cultivating strawberry plants. But it is not impossible for this plant to grow and develop well. The purpose of this community service program is to provide technical guidance to improve the knowledge and skills of Pangkalan Village young people in cultivating strawberry plants by applying climate engineering technology. The equipment given in this activity is water cooling, air conditioning, temperature and humidity control, and spray machines. This activity can be said to be successful as seen by the skills of the participants in managing tools and growing and developing strawberry plants well.